ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA AUDITOR (Studi Empiris Pada KAP Di Jawa Tengah - Venanda Aprilia P., 13.05.52.0088; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of profecionalism, experience of auditor, professional ethics, organizational commitment, understanding of good governance, and independency which directly influence acceptance of audit performance. The population in this study were all auditors working in the public accounting firm in Central Java. Sampling was done using purposive sampling method and sample size were 66 respondents. The primary data collection method used survei method was used a questionnaire . Data were analyzed using multiple linier regression model. Result of research indicate that the variablesprofecionalism,experience of auditor, professional ethics, organizational commitment, understanding of good governance, and independency have significant positive effect to audit performance.Keywords: Profecionalism, Experience of Auditor, Professional Ethics, Organizational Commitment, Understanding of Good Governance, and Independency Which Directly Influence Acceptance of Audit Performance